Novel Kazal-type proteinase inhibitors from the skin secretion of the Splendid leaf frog, Cruziohyla calcarifer - Proaño Bolaños, Carolina (2017)
Peptidase inhibitors have an important role controlling a variety of biological processes. Here, we employed a peptidomic approach including molecular cloning, tandem mass spectrometry and enzymatic assays to reveal 7 Kazal-type proteinase inhibitors (CCKPs) (18 variants) in the skin secretion of the unexplored frog, Cruziohyla calcarifer. All 18 proteins shared the Kazal pattern C-X(7)-C-X(6,7)-C-X(6,7)-Y-X(3)-C-X(2)-C-X(15-21)-C and 3 disulphide bridges. Based on structural comparative analysis, we deemed trypsin and chymotrypsin inhibitory activity in CCKP-1, 4 and CCKP 2, 5, 7, respectively. These peptidase inhibitors presumably play a role to control the balance between other functional peptides produced in the amphibian skin secretions.